2014
DOI: 10.1071/sh14181
|View full text |Cite
|
Sign up to set email alerts
|

Lower sexually transmissible infection prevalence among lifetime exclusive women who have sex with women compared with women who have sex with women and men

Abstract: While lifetime exclusive WSW are at risk of contracting STIs, WSWM are disproportionally affected. Healthcare providers should consider routine STI screening among WSW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…A U.S. population-based survey among women aged 18-59 years demonstrated an HSV-2 seroprevalence of 30% among women reporting same-sex partners during the previous year, 36% among women reporting same-sex partners in their lifetime, and 24% among women reporting no lifetime same-sex behavior (299). HSV-2 seroprevalence among women self-identifying as homosexual or lesbian was 8%, similar to a previous clinic-based study of WSW (299,305) but was 26% among Black WSW in one study (287). The relatively frequent practice of orogenital sex among WSW and WSWM might place them at higher risk for genital infection with HSV-1, a hypothesis supported by the recognized association between HSV-1 seropositivity and previous number of female partners.…”
Section: Women Who Have Sex With Women and Women Who Have Sex With Women And Mensupporting
confidence: 75%
See 1 more Smart Citation
“…A U.S. population-based survey among women aged 18-59 years demonstrated an HSV-2 seroprevalence of 30% among women reporting same-sex partners during the previous year, 36% among women reporting same-sex partners in their lifetime, and 24% among women reporting no lifetime same-sex behavior (299). HSV-2 seroprevalence among women self-identifying as homosexual or lesbian was 8%, similar to a previous clinic-based study of WSW (299,305) but was 26% among Black WSW in one study (287). The relatively frequent practice of orogenital sex among WSW and WSWM might place them at higher risk for genital infection with HSV-1, a hypothesis supported by the recognized association between HSV-1 seropositivity and previous number of female partners.…”
Section: Women Who Have Sex With Women and Women Who Have Sex With Women And Mensupporting
confidence: 75%
“…Recent studies regarding STI rates among WSW and WSWM indicate that WSWM experience higher rates of STIs than WSW, with rates comparable with women who have sex with men (WSM) in all studies reviewed (279,285,286). These studies indicate that WSW might experience STIs at lower rates than WSWM and WSM, although still at significant rates (287). One study reported higher sexual-risk behaviors among adolescent WSWM and WSW than among adolescent WSM (280).…”
Section: Women Who Have Sex With Women and Women Who Have Sex With Women And Menmentioning
confidence: 97%
“…Muzny et al 5 did not find any prevalent STIs among 21 lifetime exclusive WSW and only one woman had a history of STIs. This could be explained by the low number of exclusive WSW in the study, but seven women out of the 21 had serological evidence of Chlamydia trachomatis.…”
Section: Discussionmentioning
confidence: 89%
“…Information for these women varies from either that women with female partners are at higher risk for acquiring STIs compared with heterosexual women, to 'As you do not have intercourse you do not need any vaginal examination or routine test' written in a letter from a gynaecologist to a woman with female sexual contacts. Women engaging in same-sex sexual behaviour may be hesitant to seek testing and medical advice concerning sexual health, [1][2][3][4][5] creating challenges in estimating the risk of STIs between females due to small study cohorts. Many of these women also have sex with men, 2,4-10 and the risk of STIs is primarily associated with having male partners.…”
Section: Introductionmentioning
confidence: 99%
“…To support the evolution of origin-specific virulence, the transmissibility in women and men and/or the interactions between the sexes must differ (see Figure 5.a and Methods for examples). These biological and social differences are pervasive in human populations: differences between the sexes in infectivity and in susceptibility are ubiquitous 3,6,14,21,23,24,33 ; differences between social groups in their sex-ratios and/or their contact pattern between individuals of the same and the opposite sexes have been widely reported 27,35 .…”
Section: Discussionmentioning
confidence: 99%